Morphological and molecular identification as well pathogenicity of the causal agents of fruit rot disease of apple manalagi (Malus sylvestris) in Pujon, East Java - Unun Triasih; Abadi, Abdul Latief; Muhibbudin, Anton; Widyaningsih, Sri (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
Apple fruit rot disease is one of the major apple diseases in Indonesia. It has been caused by several species of pathogenic within the genus Colletotrichum. This research aims to identify species of the pathogen causing apple fruit rot disease in Pujon, East Java. Suspected fungal isolates were identified based on morphological (macroscopic and microscopic) and molecular characteristics. Based on the morphological observation, five isolates were identified as Colletotrichum spp. These isolates have similar morphological characteristics such as white-greyish colony color, texture colony velvety, zonation conidia concentric, round cylindrical conidial end, and conidia with 10.4–12.8 ?m in length and width 3.1–3.52 ?m, respectively. Isolates M1 showed the highest pathogenicity, therefore selected for molecular identification. Molecular identification was conducted using ITS1 and ITS4 primer, AM1 was identified as C. gloeosporioides with 99.57% similarity to C. gloeosporioides JX-19 variety from China.